CULTURE SPECIFIC ITEMS TRANSLATION STRATEGY IN ONE PIECE: ROMANCE DAWN - Andrean Susanto (Lire Journal (Journal of Linguistics and Literature), 2018)
This study investigates the translation strategy on culture specific items existed in One Piece: Romance Dawn.This study has two objectives. The first objective was to find out the CSIs in One Piece: Romance Dawn. The second objective was to find out translation strategies applied in translating the CSIs.This study was considered qualitative and a primary research. The CSIs were listed from the comic and analyzed. The result was nine CSIs found in One Piece: Romance Dawn that refers to Japanese culture.Five CSIs were written in its original Japanese word, one CSI was translated into Indonesian word, while three CSIs were shown in pictures.